Advancing regional integration migration rights of citizens in the East African community - Nalule, Caroline (My University, 2017)
This thesis attempts to identify the rationale for migration rights within the EAC (East African Community) in relation to the Community's political objectives.The main argument propounded is that migration rights, though they have developed from a purely economic rationale and perspective, have since morphed into an entorely novel regime which emphases the human or fundamental rights of citizens of the Community. [Abbreviated abstract. Taken from print version of thesis]
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2017
Keywords: Immigrants--Civil rights--Africa, East; Africa, East--Economic integration